COVID-19 SEBAGAI ALASAN FORCE MAJEURE ATAS PEMBATALAN KEBERANGKATAN UMRAH DI PT. TAZAKKA ELHAQ DITINJAU DARI KOMPILASI HUKUM EKONOMI SYARIAH (Al-Aqad, 2025)
This study aims to analyze whether the Covid-19 pandemic can be considered a force majeure under the Compilation of Sharia Economic Law (KHES) and how PT. Tazakka Elhaq responded to the cancellation of umrah departures due to the pandemic. Using a normative-empirical legal approach, the research collected primary and secondary data through interviews and documentation, analyzing the data qualitatively. The findings indicate that Covid-19 fulfills the criteria of a force majeure event as stipulated in Article 41 of KHES and can be classified as a relative force majeure, since, although umrah travel was technically still possible, the associated risks and potential losses were excessively high and beyond reasonable limits. In accordance with the Minister of Religious Affairs Regulation (KMA) No. 719 of 2020, PT. Tazakka Elhaq adopted a policy of assuming responsibility in three forms: material (refunding costs to pilgrims who canceled), moral (maintaining trust through transparent communication and service), and legal (negotiating rescheduling of departure dates for pilgrims who chose to postpone rather than cancel).